2006
DOI: 10.1353/mpq.2006.0020
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Arab American Adolescent Tobacco Use

Abstract: This study examined personal, psychosocial, sociocultural, and environmental predictors in tobacco use for 1671 Arab American adolescents. Cigarette smoking in past 30 days was 6.9%. This increased from 1% at age 14 to 14% at age 18. Twenty-nine percent of the youths reported 'ever cigarette smoking.' Experimentation with narghile was 27%; it increased from 23% at 14 years to 40% at 18 years. All trends were significant (p < .001). Logistic regression analyses found ten predictors for 'smoked a cigarette in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 19 publications
1
49
1
1
Order By: Relevance
“…This was slightly lower than estimates from Kampala, Uganda at 5.3% (Mpabulungi & Muula, 2004) but higher than that reported from Nigeria (Lawoyin et al, 2005). Our results have lower estimates compared to a study of 14-18 year olds in the United States (Rice et al, 2006) that reported that cigarette smoking in past 30 days was 6.9%. In the same study, 29% of the participants in the United States study reported to have ever smoked cigarettes.…”
Section: Discussioncontrasting
confidence: 99%
“…This was slightly lower than estimates from Kampala, Uganda at 5.3% (Mpabulungi & Muula, 2004) but higher than that reported from Nigeria (Lawoyin et al, 2005). Our results have lower estimates compared to a study of 14-18 year olds in the United States (Rice et al, 2006) that reported that cigarette smoking in past 30 days was 6.9%. In the same study, 29% of the participants in the United States study reported to have ever smoked cigarettes.…”
Section: Discussioncontrasting
confidence: 99%
“…Water-pipe use was nine times as likely to be present among those who were experimenting with tobacco than among those who were not. Surprisingly, water-pipe smoking was not correlated with parental tobacco use [41]. Similarly, Islam et al [48] performed a cross-sectional survey of 461 Muslim Arab American adolescents (12 to 19 years of age) in Virginia and were able to calculate the prevalence of susceptibility to smoking (50%), experimentation (e.g., having "ever" smoked) (45%), smoking in the last 30 days (18%), and current smoking (12%) in young adults.…”
Section: Data Synthesismentioning
confidence: 88%
“…Ancestry searches were used to identify any relevant studies that were not detected by the primary search. Because water-pipe smoking is a highly-prevalent behavior among Arabs and Arab Americans (practiced by an estimated 17% to 44.2% of this population) [10,41,42], studies that included water-pipe smoking or exclusively looked at water-pipe smoking behaviors among Arab Americans were also included. In addition, studies that included both adolescents and adults were included in this review.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Even more concerning, they found the odds of a teen experimenting with cigarettes were more than eight times greater if they had "ever smoked" a waterpipe. 16 Most studies related to prevalence are from the Middle East and Asia. If the U.S. trend grows to resemble international patterns, however, the data are disturbing.…”
Section: Perceptions/awareness/prevalencementioning
confidence: 99%